EPIDEMIOLOGY AND OUTCOME IN PATIENTS OF DIABETIC FOOT - Ashraf, M. Naeem; Rehman, Khalil -Ur-; Malik, Kamran Ishaque; Iqbal, Ghulam Sabir (Journal of Ayub Medical College Abbottabad, 2011)
Background: The aim of study was detailed analysis of the presentation of diabetic foot ulcers, characteristics and predictors of outcome (incidence of amputation in neuropathic, ischemic, neuro ischemic) in patients presenting with diabetic foot at our hospital. Methods: This prospective analytic study was conducted from January 2009-August 2010 at POF Hospital Wah Cantt. Diabetic patients who presented with foot ulcers were enrolled in this study. Demographics of patients along with ulcer size, type, site and Grade according to Wagner Classification were recorded. Wounds were managed with daily dressings, nursing care and de-sloughing of necrotic tissue along with appropriate antibiotic cover. Patients were followed over period until wound healed completely or a lower limb amputation performed, the outcome noted and patient was deemed to have completed study. Results: One hundred and fifteen patients with mean age 55.46±8.23 years, both male and female were included in this study. Out of 115 patients 111 patients had Type-II diabetes while only 4 presented with Type-I. Mean Duration of diabetes was 14.61±2.17 years. With respect to underlying causes 18.3% foot ulcers were ischemic, 22.6% were neuropathic and 59% were neuro-ischemic. Median ulcer size was 74% of ulcer classified as Wagner grade-II and III while 24% were of Grade-V. Lower limb amputation were performed in 25% of patients whereas limb salvage achieved in 75% of patients with wounds healed (median healing time 5 (3-10 weeks). Conclusion: Preservation of the limb function without endangering the patient must be a goal of treating diabetic foot. Once foot amputation is successful, rehabilitation with orthotic or prosthetic devices may allow years of a functional extremity along with preventive measures like cessation of smoking, daily foot hygiene and foot inspection. Keywords: diabetic foot, lower limb amputation, ulcer